Penerapan konseling kelompok untuk meningkatkan happiness pada remaja panti asuhan - Zainul Anwar (Jurnal Ilmiah Psikologi Terapan, 2015)
Parenting mass rearing, as well as orphanages bring a disparate impact because the current lack of guidance on the physical and mental changes occur to him, so feel anxious, confused, insecure furthermore feel lack of love, attention and supervision, making teens home care have less happiness. Observing these conditions, it would need to do the handling of juvenile orphanage in order to have a better happiness. The method used is group counseling to increase happiness in adolescents orphanage. The purpose of the study was to determine the effect of group counseling in increasing happiness in adolescents orphanage. The results showed that the mean and standard deviation of happiness between the pre and post can be seen that at the time before being given counseling group average of its happiness level is 57.38, while the average happiness after being given counseling group was 55.00. Because p-value of t test statistic is equal to 0.503 (p> 0.05), then the conclusion is the hypothesis is rejected, meaning there is no effect on the improvement of group counseling on adolescent happiness orphanage.